Late onset postpartum eclampsia without pre-eclamptic prodromi: clinical and neuroradiological presentation in two patients. Issue 6 (1st December 2000) - Veltkamp, R; Kupsch, A; Polasek, J; Yousry, T A; Pfister, H W
Abstract : In two patients eclampsia started 9 days postpartum. Headache and visual disturbances preceded seizures but none of the classic pre-eclamptic signs oedema, proteinuria, and hypertension were present until shortly before seizure onset. Brain herniation (patient 1) and status epilepticus (patient 2) necessitated neurointensive care management. Brain MRI initially showed only frontal sulcal effacement in one patient but later showed white matter hyperintensities on T2 weighted images and a previously undescribed pattern of cortical-subcortical postgadolinium enhancement on T1 weighted images in both. Neurological deficits and MRI findings were reversed with therapy in both patients. It is concluded that late postpartum eclampsia can manifest without classic prodromi and that characteristic MRI findings may lag behind clinical manifestation.